Thrombolytic and antithrombotic therapy for stroke - Bogousslavsky, Julien; Hacke, Werner (Informa Healthcare, 2006)
Thrombolytic therapy for stroke with the introduction of tissue plasminogen activator (t-PA) was a boon to stroke physicians, since it meant that morbidity and mortality could be reduced with the optimal use of t-PA. The editor and his well-respected contributors offer the reader their personal perspectives on the evidence-based use of various thrombolytic and anti-thrombotic agents that are available and that can provide successful outcomes. Up-to-date and thoroughly referenced, this clearly written text is a resource everyone working in the casualty/emergency room will want at their fingertips